2013
DOI: 10.1080/19443994.2013.822335
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chromate ion from aqueous solutions by sponge iron

Abstract: A B S T R A C THexavalent chromium ion is the most toxic form of chromium ions and it is considered as a hazardous pollutant. So removing this ion from effluents is very important. One possible approach is reducing Cr(VI) to Cr(III) by metallic iron. Sponge iron was used in this study, and the influence of parameters such as the amount of sponge iron in the solution, effect of acid washing of sponge iron, initial pH and temperature of the reaction on the efficiency of the reduction process were investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Cr(VI) [18]) include chemical precipitation and filtration [2], chemical oxidation or reduction [19,20], electrochemical treatment [21], reverse osmosis [10], solvent extraction [22], adsorption [23,24], and ion exchange [25]. These processes have several disadvantages including high operational cost, incomplete removal, low selectivity, high energy consumption, and generation of a large amount of toxic sludge to be disposed of [26,27].…”
Section: Introductionmentioning
confidence: 98%
“…Cr(VI) [18]) include chemical precipitation and filtration [2], chemical oxidation or reduction [19,20], electrochemical treatment [21], reverse osmosis [10], solvent extraction [22], adsorption [23,24], and ion exchange [25]. These processes have several disadvantages including high operational cost, incomplete removal, low selectivity, high energy consumption, and generation of a large amount of toxic sludge to be disposed of [26,27].…”
Section: Introductionmentioning
confidence: 98%
“…This is an exceedingly high value compared to the specific surface area of sponge iron obtained by conventional processes, for which a typical value of 1 m 2 /g of DRI has been reported for Schutze 55 . In a study on the removal of the chromate ion from aqueous solutions, two different DRIs, which had a surface area of 0.769 and 0.924 m 2 /g, were used successfully as catalysts 56 …”
Section: Resultsmentioning
confidence: 99%
“…55 In a study on the removal of the chromate ion from aqueous solutions, two different DRIs, which had a surface area of 0.769 and 0.924 m 2 /g, were used successfully as catalysts. 56 A study on the effect of adding biomass to iron ore pellets before burning which was subsequently reduced by hydrogen showed that the addition of 2% of biomass causes the surface area of the obtained DRI to increase from 6.03 m 2 /g without addition to 16.26 m 2 /g after the addition, and the presence of iron whiskers in the DRI was noticed. 57 Thus, it is clear that the large surface area obtained in the present work is due to the formation of iron whiskers during the reduction process.…”
Section: Carbothermal Reductionmentioning
confidence: 99%
“…It may be found as a dangerous contaminant in food, especially shellfish, liver, mushrooms, nuts and chocolate [7] [8] [9]. There are different methods for the removal of heavy metals including chemical precipitation, reverse osmosis, ion exchange, and coagulation [1] [10] [11]. However, the application of such methods is limited due to some reasons such as incomplete metal removal, energyintensive, economically expensive, and generation of secondary waste products [12] [13].…”
Section: Introductionmentioning
confidence: 99%